2018
DOI: 10.1097/hjh.0000000000001534
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone induces left ventricular subclinical systolic dysfunction

Abstract: Patients with primary aldosteronism have a lower magnitude of GLS than patients with essential hypertension, suggesting that aldosterone induces a subclinical decline in LV systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
3
25
1
Order By: Relevance
“…However, whether this LV dysfunction was caused by an excess of aldosterone or merely the effect of blood pressure was unclear [71]. In our previous study, we found that PA patients had a lower magnitude of global longitudinal strain compared to EH patients with comparable blood pressure, which indicated subclinical systolic dysfunction in PA patients [9]. This finding suggested that the effect of aldosterone on systolic function impairment was independent of hemodynamics.…”
Section: Systolic Function Evaluation In Pa: Strain Echocardiographymentioning
confidence: 88%
See 1 more Smart Citation
“…However, whether this LV dysfunction was caused by an excess of aldosterone or merely the effect of blood pressure was unclear [71]. In our previous study, we found that PA patients had a lower magnitude of global longitudinal strain compared to EH patients with comparable blood pressure, which indicated subclinical systolic dysfunction in PA patients [9]. This finding suggested that the effect of aldosterone on systolic function impairment was independent of hemodynamics.…”
Section: Systolic Function Evaluation In Pa: Strain Echocardiographymentioning
confidence: 88%
“…Subsequently, the excess aldosterone can cause more cardiovascular complications, including coronary artery disease, myocardial infarction, stroke, transient ischemic attack, atrial fibrillation and heart failure than in patients with essential hypertension (EH) [2][3][4][5][6][7][8]. In addition, it can also lead to cardiovascular remodeling and dysfunction [9][10][11]. Clinical studies have demonstrated that patients with PA have more left ventricular (LV) remodeling including increased LV mass and cardiac fibrosis than patients with EH [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Yang et al reported a higher LAVI among 100 PA patients compared to 100 EH controls [60]. Our previous investigation of left ventricular subclinical systolic dysfunction using strain analysis also showed a higher left atrial diameter and LAVI among PA patients compared to those among matched EH controls, although the difference did not reach statistical significance [61]. Wang et al recently reported increased left atrial stiffness in 107 PA patients with lower left atrial velocity, strain, and strain rate, and higher left atrial stiffness index compared to 50 EH controls [62].…”
Section: Left Atrium Structure and Functionmentioning
confidence: 76%
“…We calculated adjusted HR (aHR) values after adjusting for age, sex, Charlson comorbidity index, and propensity covariates. Death before the occurrence of diabetes was considered a competing risk event in the Fine and Gray model (12,15). To assess the difference in the diabetes-free probability curve and survival curve between the two patient groups, we analyzed competing regression plots.…”
Section: Discussionmentioning
confidence: 99%
“…New-onset diabetes was defined as one of the following conditions in those who had no history of diabetes at baseline: records of greater than three consecutive outpatient visits with the codes of prescriptions of oral antidiabetic drugs or insulin (12). Patients were monitored from the index date until death, diabetes diagnosis, 5-year follow-up period, or 31 December 2011, whichever occurred first.…”
Section: Study Outcome and Follow-upmentioning
confidence: 99%